64.8k views
3 votes
2=n-(2n+3). Solve for n. Please give steps as well.​

2 Answers

2 votes
When there is a "-" in front of the parenthesis change the sign of each term in parenthesis, Collect the like terms, Move variable to the left side and change its sign, then Move constant to the right side and change its sign, and Calculate the difference.



Answer: n=-5
User TrolliOlli
by
5.4k points
4 votes

2=n-(2n+3)

pretend that there is a -1 in front of the bracket

2=n-1(2n+3)

multiply the bracket by -1

(-1)(2n)=-2n

(-1)(3)=-3

2=n-2n-3

2=-n-3

move -3 to the other side

sign changes from -3 to +3

2+3=-n-3+3

2+3=-n

5=-n

multiply both sides by -1 to get +n

5(-1)=-1(-n)

n=5(-1)=-5

Answer:

n=-5

User Marco Stamazza
by
5.1k points